Bone Marrow Lesion: Image, Clinical Presentation, and Treatment. (12th April 2017) - Bonadio, Marcelo Batista; Ormond Filho, Alipio Gomes; Helito, Camilo Partezani; Stump, Xavier MGRG; Demange, Marco Kawamura
In this article, the cause, histology, imaging characteristics, clinical presentation, and treatment of these lesions are thoroughly discussed. Bone marrow edema is the generic term classically used to describe the high-signal-intensity alterations detected on magnetic resonance fluid-sensitive sequences. The significance of bone marrow edema for the patient's clinical condition and the prognosis of the affected joint is being increasingly investigated and discussed, and situations characterized by subchondral insufficiency are receiving increasing attention. More recent studies found some important correlations between bone marrow lesions and patient's pain and osteoarthritis progression. Conservative treatment is based on anti-inflammatory and analgesic uses according to the patient's pain, combined with reduced load on the affected limb. Regarding surgical treatment, subchondroplasty is an option still in development, albeit with promising initial results.